2007
DOI: 10.1021/jp070846q
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Electronic Structure of Peptide Bonds Using Methyl Groups

Abstract: The observed V3 torsional barriers measured by microwave spectroscopy for nine methyl groups attached alpha to peptide bond linkages in five gas-phase biomimetics have been found to differ considerably from one molecule to the next and even depend on the position of substitution, being sensitive to structural changes at the other end of the peptide bond. In the search for an explanation for these results, ab initio calculations have been performed at the HF/6-311++G(d,p) level of theory and interpreted in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Even though the presence of two internal rotors made the assignments and fitting more complicated, the two internal rotors can be treated as if there were no interacting terms connecting them, given the large geometrical distance separating them. Some evidence for the validity of this assumption has been presented in a theoretical study of a series of these model peptide systems [8]. Qualitatively speaking, we can say that each internal rotor was treated as a ''separate" molecule.…”
Section: Moleculesmentioning
confidence: 96%
See 1 more Smart Citation
“…Even though the presence of two internal rotors made the assignments and fitting more complicated, the two internal rotors can be treated as if there were no interacting terms connecting them, given the large geometrical distance separating them. Some evidence for the validity of this assumption has been presented in a theoretical study of a series of these model peptide systems [8]. Qualitatively speaking, we can say that each internal rotor was treated as a ''separate" molecule.…”
Section: Moleculesmentioning
confidence: 96%
“…A first series of fits using BELGI and fixed values for F and q will usually (provided that a decent number of both A and E transitions involving low J and K values is present in the data set) lead to satisfactory 7 These codes are available on the PROSPE web site (http://www.ifpan.edu.pl/ kisiel/introt/). 8 This ± is actually not the true parity, which is the symmetry under inversion of all coordinates, but is unfortunately commonly used in the internal rotation notation. 9 This rule may not be true if the vibrations occur in the methyl group [13].…”
Section: Constructing the Input Data Filementioning
confidence: 99%
“…However, as often pointed out, ab initio studies yield only a sort of black box, unfortunately, namely they do not clarify what physical processes are going on in the peptide linkage systems. In this respect, a recent approach by Plusquellic and Pratt [20] is worth mentioning; they pointed out by an ab initio calculation at the HF/6-311++G(d,p) level that the double-bond character of the central CAN bond of the peptide linkage is changed with the internal rotation of a methyl group attached to this bond and that there is a quasilinear correlation between the barriers to internal rotation of attached methyl groups and the relative importance of the two principal resonance structures, as mentioned in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Plusquellic [1] showed that the torsional barriers of methyl groups attached to small peptides differ considerably from one molecule to the next, and even depend upon the position of substitution. Here, we explore the origins of these effects by using chirped-pulse Fourier transform microwave (CP-FTMW) spectroscopy to determine the torsional barriers of two methyl-substituted anilines.…”
Section: Introductionmentioning
confidence: 99%